Efecto de la aplicación de bemzilaminopurina, en la propagación por abilación en plátano dominique (Musa paradisiaca). - Ordóñez Vivero, Rider Rómulo (2014)
This research was conducted, in a greenhouse located in the 21 Km of the via Esmeraldas-Quininde, enclosure ring, St. Matthew parish, canton emeralds. Geographical location: 01 ° 06' South latitude and 79 ° 27' West longitude, at an altitude of 120 meters above sea level Labour sought to determine the effects of the Benzilaminopurina (BAP) on vegetative propagation of banana dominique. We used concentrations: 0 mg/L BAP; 30 mg/L BAP; 60 mg/L BAP; 90 mg/L BAP. A "Complete at random" (DCA) experimental design was used with 4 treatments, 5 replications and 8 experimental units by treatment, from 45 days after planting were evaluated the number, length and diameter of shoots, percentage of survival and vigour of outbreaks, applying the Tukey test. After 45 days of established the trial evaluated the number, length and diameter of shoots, percentage of survival and force of outbreaks, Tukey test was applied to 5% for the evaluation of treatments. In the variable number of outbreaks, the T2 (60 mg/L BAP) concentration, reached the highest average, with 3.10 outbreaks, superior to the witness, with an average of 1.10 outbreaks. In the variable buds length treatment that attained the highest average was T3 (90 mg. / l. BAP) 49.36 cm, not found differences between the concentrations of BAP, in terms of the diameter of shoots, the concentration which attained the highest average was T2 (60 mg/L BAP), 2.22 cm. Not found differences between the concentrations of BAP. In regard to the vigor of plants, all achieved a good vigour. In terms of variable survival, there were no differences between treatments, it was between 90.40 and 84.92%. As for the economic analysis, T0 presented the lowest cost of production with mg/L BAP.